Respuesta :


you distribute the 3 to each value inside the parenthesis so it becomes 3x + 3 - 2x = -6


then combine the like terms by doing 3x-2x= x, and bringing the 3 to the other side of the equation by subtracting so the whole problem would then read, x=-9 


to check you would plug in the -9 wherever there is an x. 

3(-9 + 1) - 2(-9) = -6

3(-8) - 2(-9) = -6

-24 + 18 = -6

-6 = -6

[tex]3(x+1)-2x=-6\ \ \ |use\ distributive\ property\ a(b+c)=ab+ac\\\\3(x)+3(1)-2x=-6\\\\3x+3-2x=-6\ \ \ |use\ commutative\ property\ a+b=b+a\\\\3x-2x+3=-6\\\\x+3=-6\ \ \ \ |subtract\ 3\ from\ both\ sides\\\\x+3-3=-6-3\\\\\huge\boxed{x=-9}[/tex]

[tex]check\ (subtitute\ the\ value\ of\ x=-9\ to\ the\ left\ side\ of\ the\ \\equation:\\\\L=3(-9+1)-2(-9)=3(-8)+18=-24+18=-6=R\ \boxed{OK\ :)}[/tex]